2018
DOI: 10.1002/bjs.10832
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of an artery-first approach versus standard pancreatoduodenectomy on perioperative outcomes and survival

Abstract: The artery-first approach to pancreatoduodenectomy may be associated with improved perioperative outcomes and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(47 citation statements)
references
References 49 publications
0
44
0
3
Order By: Relevance
“…20,21 Since involvement of major visceral arteries is often a key determinant of resectability, early dissection along the arteries has become an important principle that may be associated with improved perioperative outcomes. 22 Distal pancreatectomy for pancreatic cancer mandates splenectomy in order to achieve the required lymphadenectomy, and appropriate vaccinations should be administered preoperatively. Total pancreatectomy results in type 3c diabetes, which is characterised by pancreatic exocrine and endocrine insufficiency.…”
Section: Surgerymentioning
confidence: 99%
“…20,21 Since involvement of major visceral arteries is often a key determinant of resectability, early dissection along the arteries has become an important principle that may be associated with improved perioperative outcomes. 22 Distal pancreatectomy for pancreatic cancer mandates splenectomy in order to achieve the required lymphadenectomy, and appropriate vaccinations should be administered preoperatively. Total pancreatectomy results in type 3c diabetes, which is characterised by pancreatic exocrine and endocrine insufficiency.…”
Section: Surgerymentioning
confidence: 99%
“…It should be noted that at present the available evidence for these advantages of artery‐first approaches is relatively low because it is limited to retrospective cohort studies . A recent systematic review and meta‐analysis of artery‐first versus standard pancreatoduodenectomy identified 16 retrospective cohort or case‐control studies and one very small randomized controlled trial (six vs six patients) on this topic . In the meta‐analysis of 771 artery‐first versus 701 standard pancreatoduodenectomies the intraoperative blood loss, the need for blood transfusion, the perioperative morbidity, and the rate of clinically relevant postoperative pancreatic fistula were significantly lower, while the R0 rate and overall survival were significantly higher in the artery‐first group .…”
Section: Surgical Techniques To Increase Local Radicality In Pancreatmentioning
confidence: 99%
“…Performing venous resection (VR) followed by reconstruction of the mesenteric-portal venous axis during pancreatic resections for PDAC may allow "en-bloc" resection facilitated by the superior mesenteric artery (SMA) "first" approach (34,35). Pancreaticoduodenectomies (PDs) are associated with VR in up to 25% of cases in France and Europe (less frequently in the US and more frequently in Japan).…”
Section: Commentsmentioning
confidence: 99%
“…Bachellier et al (121) reported 118 pancreatectomies (51 PD, 18 TP, and 49 DP) with ARs [CA (50), HA (29), SMA (35), and other segments (4)] including 85% with reconstruction and 89% with simultaneous VR (LE 4). Overall mortality and morbidity were 5.1 and 41.5%, respectively.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation